Survei Pola Konsumsi Protein Hewani, Sayur Dan Status Gizi Pada Mahasiswa Analis Kesehatan Poltekkes Kemenkes Bengkulu - Nika, Viora Okto; Jumiyati, Jumiyati; Yunita, Yunita (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Background: Data from the World Health Organization (WHO), records that 3.2% of adolescent girls and 5.9% of boys in the Asian adolescent population were obese in 2016. According to global data, 8.4% of adolescent girls and 12.4 % of boys are teenagers who fall into the Underweight category. 2018 Basic Health Research Data (RISKESDAS). Method: The design of this research is cross sectional. The total sample of 52 level 2 health analyst students from the Bengkulu Ministry of Health Polytechnic was taken using the simple random sampling method. Primary data includes the identity of respondents and consumption patterns of animal protein and vegetables using FFQ and for measuring body height using a microscope and weight using a step scale to determine the nutritional status of students. Results: Based on the research results, it shows that the 52 respondents often consumed 25.0% animal protein and rarely consumed 75.0%. and for vegetable consumption. Based on the research results, it shows that with 52 respondents, 32.7% often consume and rarely consume 67.3%, while nutritional status is underweight 33, normal 8, overweight 6, obese 5. Conclusion: some students have good and bad consumption of animal protein, good and bad vegetable consumption. For parents and respondents to increase the portion of vegetable and animal protein and consume a variety of animal and vegetable types more often as recommended.